Justification of Expediency to Install Own Generating Sources at Industrial Enterprises - M. A. Karatkevich; A. L. Starzhynski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper shows that reliability calculation of a power-supply system using a non-parametric method allows to distinguish highly reliable schemes at indefinite initial data and availability of own generating sources availability at an industrial enterprise. It has been determined that connection of an electric power station generator to an intemal power-supply system and provision of full enterprise capacity lead to increase of the scheme reliability by two and more fold. Higher reliability is ensured by operation of the generator on bus bars of lower voltages, namely, 0.38 or 6 kV.